Investigation of molecular markers in the diagnosis of refractory coeliac disease in a large patient cohort. Issue 11 (27th October 2008) - O'Shea, U; Abuzakouk, M; O'Morain, C; O'Donoghue, D; Sheahan, K; Watson, P; O'Briain, S; Alexander, D; Catherwood, M; Jackson, J; Kelly, J; Feighery, C
Abstract : Aims: Some patients with coeliac disease, despite strict adherence to a gluten-free diet, continue to have significant symptoms and/or a severe small intestinal histological lesion. The term "refractory coeliac disease" (rCD) is used to describe this condition. The purpose of this study was to investigate the value of tissue molecular markers reported to help in the diagnosis of rCD. Methods: Details on 61 patients with suspected rCD were collected. The clinical and laboratory findings in these patients were carefully evaluated, in part to determine whether patients were adhering to a strict gluten-free diet. The co-expression of CD3 and CD8 on intraepithelial lymphocytes was investigated by monoclonal antibody staining of small intestinal biopsy tissue; a finding of less than 50% CD3+ cells co-expressing CD8 was defined as an aberrant phenotype. T cell receptor gene rearrangement was assessed when a sufficient tissue sample was available. Results: A diagnosis of rCD was made in 38 patients based on clinical, laboratory and histological data. An aberrant intraepithelial lymphocyte population was found in 20 of these patients and in this group a clonal T cell population was found in five of seven patients tested. In the remaining 18 patients, the CD3/CD8 ratio was normal and two of seven tested had a clonal T cell population. After detailed monitoring, a diagnosis of rCD was excluded in the remaining 23 patients. Conclusions: This study supports the use of phenotypic and T cell clonality investigations in identifying patients with true rCD.